MILA ROSINTA DALAM PENCIPTAAN KARYA MATAYA INDONESIA - Ratuanak, Aloysius Rama; Christiyaningrum, Valentina Angella (Jurnal Sitakara, 2025)
This research aims to describe the creation process of the dance work Mataya Indonesia by Mila Rosinta, a well-known young dance artist in Yogyakarta. Mataya in Sanskrit means dancing and Indonesia symbolizes the diversity of the archipelago. The research method used in obtaining data is using a qualitative approach. The data were collected through interviews and literature study. This study concludes that the work Mataya Indonesia is a creation dance work created since 2012. The idea and concept of this work takes the theme of unity in the diversity of Indonesia which is poured into a dance performance. The movement motifs are inspired by the traditional dance movements of each region in Indonesia. In the creation of this work, Mila Rosinta poured several important elements such as movement, floor patterns, music, makeup and clothing, property and lighting. As a young artist, Mila Rosinta hopes that the creation of this work can motivate dance artists, aspiring artists and the younger generation to be able to create a quality and meaningful work, and still love and preserve the diversity of cultures in Indonesia. Keywords: Mila Rosinta; Dance Creation; Mataya Indonesia